Entanglement for moving three-level atom under decoherence effect - Abdel-Khalek, Sayed; Berrada, Kamal; Wahiddin, Mohamed Ridza (American Scientific Publishers, 2015)
We discuss the dynamical properties of quantum entanglement and partial entropy for moving three-level atom interacting with single-mode quantized field inside a phase-damped cavity for more general cases. The results show that the atomic motion and decoherence effects play an important role on the evolution of the system dynamics and quantum entanglement. Moreover, we show that the phenomena of long lived nonlocal correlation and short temporal disentanglement can be generated through specific values of phase damping and atomic motion parameter.